Britain and Spain: free trade, protectionism and Britain's informal empire, 1830 to 1950 - Sharman, Nick (2020)
This thesis uses Gallagher and Robinson’s concept of ‘informal imperialism’ to analyse the economic and political relationship between Britain and Spain from the 1830s to the 1950s. They viewed Britain’s imperial growth as a process of territorial expansion driven by the explosive growth of its industrial revolution and supported by its world-wide maritime dominance. To integrate new regions of the world into its industrial and trading system, British governments pursued a policy of free trade by convincing local regimes to open their economies to foreign investment and trade. Only when this preferred route of negotiation failed, did Britain turn to direct rule. This thesis argues that Spain was an early target for this form of informal free trade imperialism. Britain used a combination of commercial, diplomatic and ideological pressure, backed where necessary by military force, to open the Spanish economy to foreign trade and investment. The thesis suggests this exercise of informal British power had a significant influence on Spain’s economic and political development throughout the period, contributing to the country’s deeply unbalanced economy and consequently, to its chronic political instability. It uses a series of historical ‘windows’ to explore both these processes. In the first part, five periods of crisis in the Anglo-Spanish relationship provide illustrations of the exercise of Britain’s imperial power at crucial turning points during the growth, apogee and decline of the British Empire. The second part uses the writing and careers of six politically active economists at three key periods of change in Spain’s history to explore its reaction to the exercise of British power. The thesis suggests Spain’s protectionist movement and its subsequent evolution into increasingly radical forms of economic nationalism, represented a struggle to identify alternative development paths for the Spanish economy. It concludes that the exercise of British economic power throughout the period had an important – and often underestimated – impact on Spain’s political and economic development.